Spatiotemporal variations and driving factors of reference evapotranspiration in the Yiluo river basin - Yizhe, Li; Huiliang, Wang; Xin, Zhang; Chenhao, Li; Zihao, Tian; Qiufen, Zhang; Xizhi, Lv; Tianling, Qin (Frontiers in Earth Science, 2023)
The variations in the potential evapotranspiration (ET0) are closely related to meteorological factors. The purpose of this study is to explore the relationships between the meteorological factors and the ET0. Based on meteorological data from 26 meteorological stations in the Yiluo River Basin (YLRB) and its surrounding areas from 1958 to 2020, in this study，the temporal and spatial variations and driving factors of the ET0 in the YLRB are investigated. The results are as follows. 1. Spatially, the annual ET0 decreases from the northeast to the southwest in the YLRB. Temporally, the annual ET0 exhibits a fluctuating decreasing trend rather than a monotonic decreasing trend during the entire period. 2. The trend of the ET0 contains two mutation points, in 1972 and 1994. Thus, the research period can be divided into three periods. 3. In this study, it is concluded that the variations in the ET0 are the most sensitive to the relative humidity, but the driving factor that contributes the most to the variations in the ET0 is the wind speed. The driving factor is wind speed. 4. The driving factors are closely related to the rates of relative change of the meteorological factors.